The position of management of czech joint-stock companies on dividend policy - Sejkora František; Duspiva Pavel (My University, 2015)
The concept of distributing economic results belongs unequivocally among management’s basic financial decisions. The goal of this article is to identify factors that have a fundamental influence on dividend payout and to further determine and evaluate the position of management on dividend theories. This problematic is current for the conditions of Czech joint-stock companies, because deeper studies in this area are not available for recent years. Nevertheless, currently, the greater majority of joint-stock companies now regularly pay dividends, and dividend policy has become a part of their financial policy that is impossible to overlook. With regards to the fact that profit is the necessary condition for dividend payout, research was aimed at the sector, “Production and Distribution of Electricity, Gas and Water,” which is most interesting among Czech joint-stock companies from the perspective of profitability and frequency of dividend payout. For the reasons of quantitative research, a two-part questionnaire was created for workers in financial management – specifically, members of the executive board, who are assumed to have comprehensive knowledge and an overview of the company. The survey showed that the most important factors for management when making decisions concerning dividend payout are the following: the requirements of existing shareholders, access to funds, the actual amount of profit and maintaining the target state of debt. Further resultsconfirmed that dividend policy does infl uence fi rm value. However, dividends are not supported as a tool for lowering information asymmetry and agency costs between management and shareholders. This conclusion can becaused by ownership structure when the firms investigated are characterized by high concentration of ownership; then, one shareholder is able to better protect the other shareholders against the implementation of management’s interests.
Postoj managementu českých akciových společností k dividendové politice
Keywords: dividend policy; factors; value of the company; management; shareholders; dividendová politika; faktory; hodnota firmy; management; akcionáři